Spring habitats of small pelagic fish communities in the Bay of Biscay. (September 2018) - Doray, Mathieu; Hervy, Camille; Huret, Martin; Petitgas, Pierre
Highlights: A spatio-temporal approach of the diversity of small pelagic fish in their environment is proposed. Latitudinal and coastal-offshore spatial gradients identified in pelagic fish and hydrology. Anchovy-chub mackerel community consistently found in warmer southern spring habitat in Biscay. Small clupeiforms community found in coastal spring spawning habitats with low salinity in Biscay. Abstract: Mapping habitats of species communities helps to inform on the ecological processes which drive their distribution. This information is critical to identify suitable areas for spatial management, aimed at preserving biodiversity, ecosystem functions or essential habitats. While demersal fish have been extensively studied at the community scale, small pelagic fish have mainly been characterised at the population scale. This paper presents a community-based approach on the biodiversity of small pelagic fish, with the aim to: (i) define small pelagic fish communities, (ii) characterise their spatial and interannual dynamics, and (iii) assess their habitats. We present a Multiple Factor Analysis (MFA)-based method that characterises the spatio-temporal variability in a series of multivariate maps. The main components of variability in these maps are identified to define "characteristic areas" displaying contrasting conditions in both MFA ordination and geographical spaces. Characteristic habitats of fish communities were defined by the correlation between the main components of variability from MFAs applied to maps containing fish information on one hand, and on hydrographic variables on the other hand. The analysis of the long term PELGAS survey series of fish biomass and hydrological indices maps resulted in the characterisation of mesoscale latitudinal gradients and coarse to mesoscale onshore-offshore gradients in both fish and hydrology datasets. A community with anchovy ( E. encrasicolus ) and chub mackerel ( S. colias ) as indicator species was consistently distributed in southeast Biscay. This area was associated with higher bottom temperatures, which likely affected the fish community through physiological processes. A second community with small clupeiforms as indicator species was found in coastal spawning habitats. These habitats were typically characterised by low salinity, a probable proxy for high productivity and good feeding grounds for those species. Mapping the habitats of small pelagic fish communities may inform marine spatial management, aimed at preserving biodiversity, ecosystem structure and function. In addition, it may help in achieving maximum sustainable yields of these commercially important species, and contribute to achieving and maintaining good environmental status of shelf seas ecosystems.